The Implementation of the Arabic Language Environment (Bi’ah ‘Arabiyah) as a Strategic Model for Developing Students’ Communicative Competence at Hidayatullah Islamic Boarding School Lombok - Laelatul Fitri; Mukhlishin Mukhlishin; M. Syahrul Izomi (FKIP - Universitas Riau, 2026)
This study aims to analyze the implementation of the Arabic language environment as a strategic model for developing the communicative competence of students in Islamic boarding schools. The research focuses on the role of linguistic discipline in daily interactions and the effectiveness of structured and cultural language practices in shaping students’ Arabic-speaking behavior. Using a qualitative descriptive design with an ecological linguistic perspective, data were collected through in-depth interviews, non-participant observations, and document analysis involving school leaders, language coordinators, teachers, supervisors, and students. Thematic analysis was employed to identify implementation patterns, disciplinary mechanisms, communicative achievements, and contextual challenges. The findings show that the Arabic language environment functions as a cultural-linguistic system integrating structured discipline such as language zones, monitoring, corrective measures, and regular evaluation with everyday language practices supported by teacher modeling, peer interaction, and routine activities. Linguistic discipline significantly enhances students’ fluency, accuracy, confidence, and vocabulary development. Despite its effectiveness, implementation faces challenges related to teacher competence, inconsistent language use, limited facilities, and diverse student backgrounds.